(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the feasibility of applying ChatGPT as an artificial intelligence application in higher education institutions in Zuwara City, within the context of digital transformation in education, The study adopted a descriptive analytical approach and used a questionnaire as the primary data collection tool, targeting faculty members in higher education institutions, with a valid sample of 164 respondents, Data were analyzed using SPSS, The findings indicate a high potential for implementing ChatGPT in higher education, due to its role in enhancing self-learning, improving educational content quality, and supporting faculty members in academic tasks, However, several challenges were identified, including weak technological infrastructure, limited awareness of proper use, and ethical concerns regarding information accuracy, The study recommends integrating ChatGPT into higher education strategies, enhancing digital infrastructure, providing training programs, and establishing ethical and regulatory frameworks to ensure responsible use.